The rise of big data policing: surveillance, race, and the future of law enforcement - Ferguson, Andrew G. (New York University Press, 2017)
Introduction : big data policing -- Big data's watchful eye : the rise of data surveillance -- Data is the new black? : the lure of data-driven policing -- Whom we police : person-based predictive targeting -- Where we police : place-based predictive policing -- When we police: real-time surveillance and investigation -- How we police : datamining digital haystacks -- "Black data?" : distortions of race, transparency, and law -- "Blue data?" : policing data -- "Bright data?" : risk and remedy -- No data : filling data holes -- Conclusion : questions for the future